Safe Space in Times of Post-Modernity: On the practice and dynamics of Neo-Diasporic Communities (KULT_online, 2023)
In her book, Neo-diasporische Gemeinschaften: Blouzaniyye in Sydney, Australien, Marie Johanna Karner presents a new diaspora theory that considers the dynamics of the 21st century and offers new perspectives on actors, collective narratives, and community-building practices. The author develops the theory through empirical, interdisciplinary, and multi-method research on Lebanese Maronite diasporic communities.